2009
DOI: 10.1007/s12665-009-0017-5
|View full text |Cite
|
Sign up to set email alerts
|

Clay fine fissuring monitoring using miniature geo-electrical resistivity arrays

Abstract: This article describes a miniaturised electrical imaging (resistivity tomography) technique to map the cracking pattern of a clay model. The clay used was taken from a scaled flood embankment built to study the fine fissuring due to desiccation and breaching process in flooding conditions. The potential of using a miniature array of electrodes to follow the evolution of the vertical cracks and number them during the drying process was explored. The imaging technique generated two-dimensional contoured plots of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 13 publications
2
25
0
Order By: Relevance
“…8b and 9b show high resistivity anomalies corresponding with the positions of the fissures, contrasted with the lower resistivity of the intact soil. The results are consistent with the findings of previous works (Samouelian et al, 2003(Samouelian et al, , 2004Sentenac and Zielinski, 2009). Clear similarities can be seen between the shape and position of the high resistivity anomalies on the top surface of the resistivity models and the fissuring network observed on the physical soil model: the grids applied to the displayed models show that the position and lengths of the major fissures are consistent.…”
Section: Surface Fissuringsupporting
confidence: 91%
See 2 more Smart Citations
“…8b and 9b show high resistivity anomalies corresponding with the positions of the fissures, contrasted with the lower resistivity of the intact soil. The results are consistent with the findings of previous works (Samouelian et al, 2003(Samouelian et al, , 2004Sentenac and Zielinski, 2009). Clear similarities can be seen between the shape and position of the high resistivity anomalies on the top surface of the resistivity models and the fissuring network observed on the physical soil model: the grids applied to the displayed models show that the position and lengths of the major fissures are consistent.…”
Section: Surface Fissuringsupporting
confidence: 91%
“…Previous studies (Samouelian et al, 2003(Samouelian et al, , 2004Sentenac and Zielinski, 2009;Zielinski et al, 2011) have used Electrical Resistivity Tomography (ERT) to image fissures forming in the soil subsurface. Samouelian et al (2003) first showed the sensitivity of ERT in mapping artificially created 2-D fissures in a silty loam.…”
Section: Resistivity and Fissuringmentioning
confidence: 99%
See 1 more Smart Citation
“…If cracks do initially seal at the soil surface, the utility of surface‐based crack measurements (Zein el Abedine and Robinson, ; Ringrose‐Voase and Sanidad, ; Návar et al ., ; Wells et al ., ; Arnold et al ., ; Abou Najm et al ., ) may be limited. Instead, techniques that monitor subsurface crack dynamics, such as electrical resistivity tomography (ERT) (Samouëlian et al ., ; Samouëlian et al ., ; Amidu and Dunbar, ; Sentenac and Zielinski, ; Greve et al ., ; Greve et al ., ), or physically installing subsurface monitoring instruments into representative cracks (Stewart et al ., ) may prove more informative about the rate and degree to which cracks close.…”
Section: Introductionmentioning
confidence: 99%
“…() recorded and displayed by the resistivity equipment all the major vertical cracks (of centimetre size), which have been visually observed at the surface of the clay model. Sentenac and Zielinski () studied 2 mm–4 mm wide fissures in clay with a miniature ERT system. Lataste et al .…”
Section: Introductionmentioning
confidence: 99%